Religious Moderation and Religious Traditions in Post-Death Grief in Munggu Village, Central Bangka Regency - Ulum, Miftahul; Rozi (Institut Agama Islam Negeri Ponorogo, 2025)
In Indonesia, a tolerant attitude towards local culture can give birth to an inclusive and tolerant religious attitude, creating a peaceful and dynamic atmosphere of spiritual life. On the other hand, religion must exist, penetrate, and spread to influence the cultural appearance of society, without eliminating its cultural identity. In this way, religion and local culture are interrelated and complement each other; this is reflected in religious wisdom and cultural attitudes that are developed based on religion. This research uses field research, namely observations or observations involving researchers in the field. The data collection techniques used are interviews, observation, and documentation, with the research subjects being the local community who carry out post-death care. This research uses field research, namely observations or observations involving researchers in the field. The data collection techniques used are interviews, observation, and documentation, with the research subjects being the local community who carry out post-death care.